Chirocentrodon bleekerianus (Teleostei: Clupeiformes: Pristigasteridae), a small predaceous herring with folded and distinctively oriented prey in stomach - Sazima, C. [UNESP]; Moura, R. L.; Sazima, I. (Instituto Internacional de Ecologia, 2004)
Predaceous fish-eating species of the order Clupeiformes have a large mouth with well-developed teeth, and reach the greatest sizes within their families (up to 90 cm). We found that the pristigasterid Chirocentrodon bleekerianus, a small clupeiform (about 10 cm) from the tropical SW Atlantic, is able to prey on proportionally large clupeoid fishes and caridean shrimps. Fish preys are folded in the stomach of this herring, their heads and tails pointing toward the predator's head. This distinctive orientation of fish prey is also recorded for some small to medium-sized, fish-eating species of the tropical freshwater order Characiformes with canine-like teeth similar to those found in C. bleekerianus.

Dentre os Clupeiformes, as espécies piscívoras apresentam boca grande, com dentes bem desenvolvidos, e alcançam os maiores portes dentro de suas famílias (até 90 cm). Registramos que o pristigasterídeo Chirocentrodon bleekerianus, um clupeiforme de pequeno porte (cerca de 10 cm) do Atlântico Sul Ocidental, apresa peixes e camarões proporcionalmente grandes. Os peixes ingeridos ficam dobrados no estômago dessa sardinha, com suas cabeças e caudas em direção à cabeça do predador. Essa orientação distinta de presas também ocorre em algumas espécies piscívoras de Characiformes de pequeno a médio porte, que apresentam dentes caninos similares aos encontrados em C. bleekerianus.
Chirocentrodon bleekerianus (Teleostei: Clupeiformes: Pristigasteridae), uma sardinha predatória de pequeno porte que apresenta suas presas dobradas e orientadas no tubo digestivo
Keywords: Clupeiformes; predaceous habits; piscivory; folding of prey; convergence; Clupeiformes; hábitos predatórios; piscivoria; dobramento de presas; convergência